Flow characteristic of steam jet condensed into a water pipe flow - a numerical study. (25th March 2022) - Xu, Qiang; Zhu, Yongshuai; Zhou, Haozu; She, Yonglu; Guo, Liejin
Highlights: Numerical simulation of steam jet condensation in subcooled water flow is conducted. Thermal hydraulic parameters of cone and cylinder-cone steam plumes are analyzed. The total pressure in the centerline reaches maximum at steam volume fraction 0.01. Heat transfer coefficients based on area and volume of two-phase region are obtained. Abstract: Gas-liquid two-phase jet condensation has a property of high heat and mass transfer efficiency, thereby its theory and method becoming an urgent requirement for optimization design and safe operation of various industrial processes. Based on the experimental study of steam jet condensation in subcooled water flow in a vertical pipe, we have developed a numerical simulation method of steam-water two-phase jet condensation coupled with thermal phase change model and two-fluid model. Meanwhile, we emphasize on the shape of the steam plume, the distribution of pressure and velocity, and the heat and mass transfer of the two-phase interface. As the steam mass flux increases from subsonic to sonic, the steam plume becomes longer, and its shape transforms from cone to cylinder-cone gradually. The steam volume fraction is close to 0.01 at the end of the two-phase region, where the total pressure in the centerline approaches the total pressure of the water and reaches the maximum. The mass transfer process of steam condensed into liquid mainly occurs in the gas–liquid two-phase region, accompanied by drastic parameter change in pressure and velocity. Under the working conditions of this paper, the heat transfer coefficients based on the interfacial area of the steam plume and the volume of the two-phase region range from 1.71 MW/m 2 K to 3.51 MW/m 2 K, and from 2398.80 MW/m 3 K to 5040.07 MW/m 3 K, respectively.